Microstructure-dependent charge carrier transport of poly(3-hexylthiophene) ultrathin films with different thicknesses - Janasz, Lukasz; Marszalek, Tomasz (Langmuir, 2017)
Since the interfacial order of conjugated polymers plays an essential role for the performance of field-effect transistors, comprehensive understanding on the charge carrier transport in ultrathin semiconducting films below thicknesses of 10 nm is required for the development of transparent and flexible organic electronics. In this study, ultrathin films based on poly(3-hexylthiophene) as conjugated polymer model system with a thickness range from single monolayer up to several multilayers are investigated in terms of microstructure evolution and electrical properties of different molecular weights. Interestingly, a characteristic leap in field-effect mobility is observed for films with thickness greater than four layers. This threshold mobility regarding film thickness is attributed to the transition from 2D to 3D charge carrier transport along with an increased size of the P3HT aggregates in the upper layers of the film. These results disclose key aspects on the role of the film interlayer on the charge carrier transport through conjugated polymers in transistors.
Gesehen am 10.07.2018